Views from abroad; European perspectives on American art 1.-Amerikaanse perspectieven; Europese visies op Amerikaanse kunst 1. - Fuchs, R.; Weinberg, A.D. (New York : Whitney Museum of American Art, 1995)
Lüpertz, Markus ; Guston, Philip ; Hartley, Marsden ; Kline, Franz ; Luks, George ; Appel, Karel ; Förg, Gunther ; Marin, John ; Rauschenberg, Robert ; Benton, Thomas Hart ; Warhol, Andy ; de Kooning, Willem ; Salle, David ; Kelly, Ellsworth ; Sheeler, Charles ; Saura, Antonio ; Kounellis, Jannis ; Hartley, Marsden ; Johns, Jasper ; Stella, Joseph ; Judd, Donald ; Byars, James Lee ; Reinhardt, Ad ; Rainer, Arnulf ; Kirkeby, Per ; Ryman, Robert ; Sloan, John ; Dubuffet, Jean ; Gilbert & George
boek